Review of the genus Earinus Wesmael (Hymenoptera, Braconidae, Agathidinae) from China - Tang, Pu; van Achterberg, Cornelis; Chen, Xue-Xin (Zootaxa, 2018)
The Chinese species of Earinus Wesmael, 1837 (Braconidae, Agathidinae) are revised and eight species are recognized. Three new species, namely, E. longigena sp. nov., E. pallitarsus sp. nov. and E. protinus sp. nov., are described and illustrated, and two species are recorded from China for the first time, i.e., E. brevistigmus van Achterberg et Long, 2010 and E. elator (Fabricius, 1804). A new synonym is proposed, Earinus albopilosus Chen et Yang, 2006, with Therophilus festivus (Muesebeck, 1953). A key to the Chinese species of the genus Earinus is provided.